Building for tomorrow - Cattermole, Paul (London Thames & Hudson, 2013)
Architects have always dreamed of shaping the future, of building utopian worlds filled with seemingly impossible structures that break with the past to propel mankind far into the 21st century and beyond. This book reviews forty such visionary projects, encompassing the whole spectrum of the built environment, from bus stations and concert halls to boat lifts and aquariums. This stimulating survey, illustrated with the very best architectural photography, will transport readers into yet unknown worlds.
Keywords: WORLDS; ANCIENT; ORGANIC; ALIEN; DEATH STARS; TIE FIGHTERS; BLOB; MECHANICAL; MANMADE; MENACING; SUSTAINABLE; SLEEK; ARCHITECUTRE HISTORY (ARC-HIS)